Electrochemical Micromanufacturing of Copper/Graphene Oxide Composites - Zhang, Kaituo (My University, 2023)
Electrochemical Additive Manufacturing (ECAM) is a simple and efficient micro 3D metal manufacturing method that nowadays has great potential in various areas, especially in functional materials such as electrode materials. However, maintaining a steady water droplet connection between the printing nozzle and substrates is indeed a challenge in the current meniscus-confined ECAM technique. In order to better control the droplet formation for micro ECAM, to enhance the meniscus stability and to simplify the process, this work introduces cellulose based gels as novel precursors for ECAM to fabricate copper (Cu) on different substrates. In addition, different levels of Graphene Oxide (GO) were added to improve the structural and electrochemical properties of the deposits, i.e. corrosion resistance. The effects of GO in the Cu-based deposits were investigated in detail by Scanning Electron Microscopy (SEM), Raman Spectroscopy, X-ray Photo-electron Spectroscopy (XPS), Cyclic Voltammetry (CV) and corrosion tests, including surface morphology and composition analysis, as well as corrosion resistance in 3.5% NaCl solution. Ultimately, gel-like precursors suitable for the micro ECAM process were successfully prepared. A series of samples with GO content of 0.1 - 3.0 wt.% of copper ions were then prepared on this basis, and in comparison with pure Cu samples, it was concluded that GO reduced the corrosion current density by 26.6% to 65.6%.
Keywords: electrochemical additive manufacturing; electrochemical deposition; gel precursors; 3D printing; graphene oxide; corrosion test